(E)-3-(2,4-Dimethoxyphenyl)-1-(3,4-dimethoxyphenyl)prop-2-en-1-one - Xiaokai Wu; Xiaoqing Cai; Xianan Zheng; Zhennan Zhang; Xiaoqin Ye (Acta Crystallographica Section E, 2010)
The title compound, C19H20O5, is approximately planar; the dihedral angle between the benzene rings is 3.82 (8)°, and the central propenone C(=O)—C=C plane makes dihedral angles of 1.95 (10) and 3.17 (11)° with the two benzene rings. In the crystal structure, intra- and intermolecular C—H...O hydrogen bonds are observed.